Security framework for Android applications - Sim, Geric Wei Siang (2015)
Frauds, infringement of privacy, hacking, loss of data and many more acts are somethings everyone faces in modern society. One of the biggest issue is mobile security, in this case the focus is on the Android platform, given its wide spread usage it is important to build safeguards for it. There are many security applications out there in the market and this application would not be out of the original. It would seek to put in place Rules that would mimic current identifiers of security breaches that could only be used on a more capable device like a workstation. The outstanding thing about this app is that it is an informative app which seeks to place as much details to the user, hoping it will allow the user to know of the dangers with in the device. This is still first and foremost, a work-in progress and the first in it iteration. The whole idea is based on the noble and tedious task to weed out malicious apps that might be rampaging through private data and to hopefully in future put a stop to it.